B-Cell RANKL Contributes to Pathogen-Induced Alveolar Bone Loss in an Experimental Periodontitis Mouse Model - Settem, Rajendra P.; Honma, Kiyonobu; Chinthamani, Sreedevi; Kawai, Toshihisa; Sharma, Ashu (Frontiers in Physiology, 2021)
Periodontitis is a bacterially-induced inflammatory disease that leads to tooth loss. It results from the damaging effects of a dysregulated immune response, mediated largely by neutrophils, macrophages, T cells and B cells, on the tooth-supporting tissues including the alveolar bone. Specifically, infiltrating B cells at inflamed gingival sites with an ability to secrete RANKL and inflammatory cytokines are thought to play roles in alveolar bone resorption. However, the direct contribution of B cells in alveolar bone resorption has not been fully appreciated. In this study we sought to define the contribution of RANKL expressing B cells in periodontitis by employing a mouse model of pathogen-induced periodontitis that used conditional knockout mice with B cell-targeted RANKL deletion. Briefly, alveolar bone loss was assessed in the wild-type, B-cell deficient (Jh), or B-cell-RANKL deleted (RANKLΔB) mice orally infected with the periodontal pathogen Tannerella forsythia. The RANKLΔB mice were obtained by crossing Cd19-Cre knock-in mice with mice homozygous for conditional RANKL-flox allele (RANKLflox/flox). The alveolar bone resorption was determined by morphometric analysis and osteoclastic activity of the jaw bone. In addition, the bone resorptive potential of the activated effector B cells was assessed ex vivo. The data showed that the RANKL producing B cells increased significantly in the T. forsythia-infected wild-type mice compared to the sham-infected mice. Moreover, T. forsythia-infection induced higher alveolar bone loss in the wild-type and RANKLflox/flox mice compared to infection either in the B cell deficient (Jh) or the B-cell specific RANKL deletion (RANKLΔB) mice. These data established that the oral-pathogen activated B cells contribute significantly to alveolar bone resorption via RANKL production.